CYCLE-TO-CYCLE VARIATIONS OF THE SYMBIOTIC BINARY R AQR - Chinarova, L. L; Andronov, I. L.; Schweitzer, E. (Одеські астрономічні публікації, 2017)
The observations of R Aqr from the AFOEV database are analyzed. The corrected value of the period P = 387509 ±0.029d was determined from a 5-th order trigonometric polynomial fit with a corresponding initial epoch for the maximum To =244473376 ±0.93d and asymmetry A =0.409 ±0.011. The cycle-to-cycle variations of the phase curve are present which are studied by using ”running parabolae”, ”running sines”, ”asymptotic parabolae” and ”linear fit” approximations. The range of variations is 5.7-8.01m (brightness at maximum), 10.6-12.3m (brightness at minimum), 7.1 - 34.1 days/mag (slope of the ascending branch at m : 9m); 25.7 - 44.6 days/mag (slope of the descending branch at m = 9m). The corresponding full amplitudes of the phase variations are 0.069; 0.136, 0.12o, 0.256, respectively. The most stable in phase is the maximum, for which no secular period variations detected, but a secondary cycle of P2=3955 ±50d and amplitude (0.032 ±0.005)P may be suggested. The characteristics of the individual cycles are tabulated.